The Ability of Human Resources in Compiling Financial Reports at the Ministry of Religion Office of Sabang City - Eddi Fahmi; Ismail; T. Syarifuddin (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
Enhancement ability human resources of service officers at The Ministry of Religion Office of Sabang City has so far been carried out in two ways, namely through education and training. Then also carried out an increase in ASN discipline in the preparation of financial reports so that employees doing their duties in a timely manner, with the right quality and comply with applicable regulations. The purpose of this research are to find out and analyze the improvement of ASN's ability in compiling financial reports at the Ministry of Religion Office of Sabang City and to find out and analyze the improvement of ASN discipline in the compiling financial reports at the Ministry of Religion Office of Sabang City. Researchers used qualitative methods in order to collect data with the technique of determining the informants was done by purposive sampling. The results showed that ASN ability still low, especially with regard to the level of education and training. Then civil servant discipline at the Ministry of Religion Office of Sabang City is still low, especially regarding getting to the office on time, this is still often not appropriate, as well as with the right quality because it is not on time then automatically it is not of the right quality, but employees obey the applicable rules. The conclusion of the study shows that Education is an important factor in improving human resources at the Ministry of Religion Office of Sabang City, but higher education is not a guarantee for someone to be placed in a structural position by the head. Then related to the training attended by the employees of the Ministry of Religion of Sabang City, they participated in various trainings and usually one training lasted for four days. Employees at the Ministry of Religion Office of Sabang City are still not disciplined in their work because they enter the office not on time, and return home not on time so that the results are not of the right quality but other rules are obeyed and obeyed. In terms of responsibility, they are still low, but they have a good attitude at work.